Calculation of the influence of friction resistance face plate attenuation plane jet - Толеуов, Г.; Исатаев, М.С.; Оспaновa Ш.С. (Recent Contributions to Physics, 2016)
In the study of the jet plane the experimental devices, as a rule, to eliminate the influence of the height of the limb of a rectangular nozzle flow field end plate limited. Sets the plates parallel to the direction of flow, as an extension of the outlet section of a rectangular nozzle end walls. The paper shows the results of the calculation of the effect of mechanical friction plates on the laws of development of the jet plane free. Built jet flow pattern bet ween the end surfaces. Spend resistancecalculation in the turbulent boundary layer. Calculating formula is obtained which describes the maximum change in velocity of the jet in the first approximation. Comparison of the calculation results with the experimental data.